Richard, Fred, Kenneth, Michael and them Sir Richard Rodney Benneth talks about ballet scores - Jackson, Paul R. W. (Dance Books Ltd., Alton,Hampshire (UK), 2004)
Sir Richard Rodney Benneth talks about ballet scores. Bennett vividly remembers crying uncontrollably over Walter Gore's Winter Night - which was terribly embarrassing for a young child. In Bennett MacMillan found a worthy collaborator who fulfilled all of his musical needs as few others could. This passionate, verdant, romantic work surely contains some of the most erotic music ever written by an Englishman. PALABRAS CLAVE: Richard Rodney Bennett, British music, Frederick Ashton, Kenneth MacMillan, Michael Corder, ballet scores.